Plastic pandemic: how distributed ledger technology and the internet of things can create a circular economy of plastics - Sankaran, Krishnaswamy (Henry Stewart Talks, 2022)
The plastic pandemic, Problems and solutions, Supply and value chain, The value of recycling, Circular economy of plastics, Multi-sensor IoT platform and Distributed Ledger Technology (DLT) tools, Managing commingled plastic waste, Smart recycling supply chains